Clinical risk factors associated with ventricular fibrillation during first ST-elevation myocardial infarction. (19th May 2022) - Warming, PE; Glinge, C; Jabbari, R; Stampe, NK; Dusi, V; Tan, HL; Bezzina, CR; Crotti, L; De Ferrari, GM; Engstrom, T; Schwartz, PJ; Wilde, AAM; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation programme under acronym ESCAPE-NET, registered under grant agreement No 733381 Introduction: Sudden cardiac death (SCD) remains a major public health issue. Most cases in the general population are caused by ischemic heart disease, and often occur in patients without known ischemic heart disease. The assessment of risk factors may point to novel causal pathways or new targets for intervention and risk prediction of SCD. Objective: The aim of this study was to evaluate the effect of family history of sudden death, prior history of atrial fibrillation (AF), and anterior infarct location on ECG on the development of ventricular fibrillation (VF) during first ST-elevation myocardial infarction (STEMI). Methods: We performed individual participant data meta-analyses of three European case-control studies including first STEMI patients (aged 18-80 years) with VF (cases) and without VF (controls) before revascularization (GEVAMI, AGNES, and PREDESTINATION). Analyses were done using fixed-effect, inverse variance weighted meta-analysis and multivariable logistic regression. Potential confounding variables were identified using causal diagrams and missing data were handled with multiple imputation for each cohort separately. Results: We included 1664 cases and 2497 controls (median age (IQR) = 59 (51-67) years, 20% females) in the analyses. After adjusting for potential confounding, we found an independent and additive association between the three exposures and VF (see picture): for family history of sudden death odds ratio (OR) 1.59 (95% confidence interval: 1.37-1.85), for AF OR 2.41 (1.49-3.89), and for anterior myocardial infarction OR 1.50 (1.32-1.71). Further investigation indicated increased effect of family history with multiple sudden deaths in the family, a stronger effect of AF on VF developing within the first minutes of symptoms, and the effect of anterior infarctions being modified by enzymatically determined infarct size. The three risk factors showed an additive effect: with one factor present OR 1.59 (1.38-1.84), two factors OR 2.41 (1.95-2.99), and all three factors OR 5.49 (1.43-21.1). Complete case analysis gave similar results for all analyses. Conclusions: Family history of sudden death, history of AF, and anterior infarct location with significant interaction with enzymatic infarct size were all independently and additively associated with an increased risk of VF in patients with a first STEMI.